Cognitive abilities in a sample of young Swedish children - Clausén Gull, Ingela; Stålnacke, Johanna; Eninger, Lilianne; Ferrer-Wreder, Laura; Eichas, Kyle (Frontiers in Psychology, 2024)
Cognitive abilities are closely related to social emotional competences (SEC). These abilities are important foundations in order to adapt to school, interact with peers and adults, as well as to navigate the wider socio-cultural context in which one develops. Further, young children are also acquiring and deepening their language and preliteracy skills which are important for later academic learning. Central to cognitive abilities are the processes that enable deliberate and goal-oriented actions, which fall under the conceptual umbrella of executive functions (EFs). In this study, we applied a conceptually broad perspective to examine cognitive abilities, preliteracy and SEC in preschool aged children. Children were participants in an intervention trial of the preschool edition of Promoting Alternative Thinking Strategies (PATHS®) conducted in preschools located in three municipalities within a large city in Sweden. Pre-test data were used to examine cognitive abilities and SEC in this sample of Swedish 4 to 5-year-old children (N = 247). We first performed an exploratory factor analysis including the wide range of examined abilities, and found that measures of abilities typically viewed as SEC, did not group with measures of preliteracy skills and abilities typically considered as EFs. Second, we performed confirmatory factor analyses on remaining relevant indicators of cognitive abilities, which indicated a two-factor model best fit the data, with one factor involving inhibitory control and one factor involving more complex and high-demanding skills (working memory, cognitive flexibility, and preliteracy skills). Results indicated that more complex EFs and preliteracy skills were closely linked, and can be differentiated from inhibitory control, already in the preschool years. Findings also point to the importance of including a broad range of cognitive abilities (e.g., pre-literacy skills) in order to gain a nuanced description of possible interrelations between cognitive and social emotional development. Furthermore, this study contributes to the theoretical discussion on EF structure during childhood, and provides a sound empirical rationale for the further development of early interventions that consider young children’s executive functions and preliteracy skills.